Micro electret power generator for ambient vibration energy harvesting - Liu, Shuwei (2014)
Ambient vibration sources are commonly available in abundance and characterized by low-level vibration of low frequency (<100Hz) and small acceleration (<0.1g). Vibration energy harvested from ambient environment offers a promising sustainable alternative or complementary source of power for electronic devices and systems such as wireless integrated sensor (WINS) nodes that require low power consumption. This is particularly so if they are to be used in embedded environment where maintenance of such devices and systems can be a challenge. Electret-based electrostatic power generators, named micro electret power generators in this work, are explored as they are more compatible with the CMOS MEMS technology hence can be more easily fabricated in batches. As energy harvesters, micro inertial electret power generators with spring-mass structure can magnify the ambient vibration amplitude from several micro meters to hundreds of micro meters at resonance. Nevertheless, it was observed that its harvesting effectiveness would reduce drastically to minimal and unstable at very small volumes and low frequencies. From reviews conducted, it was reported that it would be a great challenge to achieve effectiveness of 5% at frequency less than 100Hz within volume less than 1cm3. This thesis presents a novel sandwich structure in-plane inertial micro power generator with two capacitive configurations sharing a moveable mass plate in the middle that can operate effectively at low ambient vibration frequencies. The design of micro generator has necessitated the establishment of new theoretical formulation and modelling of the capacitance change and electromechanical coupling, adoption of new resonant spring-mass design configurations and charging methods for material fabrication. For the vibration-mechanical interface, various spring configurations have been explored. Two spring configurations with folded beams have been designed and developed that are able to operate at resonant frequencies of less than 100Hz. Besides this, a three dimensional finite element model with fringing field effect incorporated is established for studying the electromechanical coupling for the parallel plate capacitive configuration of a power generator. From analysis based on the approach, two capacitive configurations with phase difference of π are found to reduce the restoring effect of electrostatic force on the dynamics of mass motion and therefore enhance the electromechanical coupling leading to improved electrical outputs. To form micro electret array with high and stable surface potential, a new localised charging method has been developed with good charging efficiency, charge stability and slow charge decay characteristics for micro sized electrets. Experimental tests conducted on micro sized electrets (100um×100um) had found that its charge potential remains stable for a period of 240 days. A novel characterization approach for surface potential estimation on the micro-sized electrets has also been formulated. The approach is able to accurately map and evaluate the various charge distribution areas of the charged sample. In fabrication of parallel-plate micro electrets power generators using silicon micromachining techniques adopted in MEMS technology, a double-sided alignment method is able to achieve pattern alignment error of less than 0.6µm. Measurements conducted found that the pin and hole alignment approach can achieve a plate assembly error of less than 5 µm. In addition, heat management has been carried out in the fabrication process of spring-mass structure to increase the fabrication yield and accuracy. Experimental results have revealed that with good heat management involving the appropriate design of heat blocks, fabrication yield can be increased to 100%. Smaller deviations from the designed resonant frequencies are also observed from a reported figure of 43.7% to 26% therefore enabling greater predictability in design. A micro electret power generator prototype integrated with locally charged LDPE thin film based on a sandwich structure containing two capacitive configurations has been fabricated and assembled. The prototype can generate more than three-fold increase in power output from a single capacitive configuration compared to a conventional two-plate power generator for quite similar set of design parameters. The sandwich structured power generator is also able to achieve a harvesting effectiveness of 7% within a volume of 0.35cm3 at frequency of 44.2Hz having a mechanical quality factor of 89. In another experiment conducted, a two-plate micro electret power generator based on an outward type II S-spring configuration can even harvest the 48th harmonic component of a low vibration frequency of 2Hz with appreciable amount of electrical output. The quality factor for this configuration is however substantially higher at 121.